2014
DOI: 10.1097/ta.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence concussion knowledge and self-reported attitudes in high school athletes

Abstract: BACKGROUND Many organizations and health care providers support educating high school (HS) athletes about concussions to improve their attitudes and behaviors about reporting. The objectives of this study were to determine if previous education, sport played, and individual factors were associated with better knowledge about concussion and to determine if more knowledge was associated with improved self-reported attitudes toward reporting concussions among HS athletes. METHODS We conducted a survey of HS ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
95
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(108 citation statements)
references
References 32 publications
6
95
7
Order By: Relevance
“…8,[20][21][22] Factors such as athletes' beliefs and the attitudes of coaches, teammates, and parents are important. 4,[6][7][8]10,11,17,28 Our results also do not fully support these 2 assumptions. Athletes who received concussion education and had experienced a concussion did not report having sought medical treatment at a statistically higher rate than those without training, in agreement with other studies.…”
Section: Effectiveness Of Concussion Education and Trainingcontrasting
confidence: 46%
See 1 more Smart Citation
“…8,[20][21][22] Factors such as athletes' beliefs and the attitudes of coaches, teammates, and parents are important. 4,[6][7][8]10,11,17,28 Our results also do not fully support these 2 assumptions. Athletes who received concussion education and had experienced a concussion did not report having sought medical treatment at a statistically higher rate than those without training, in agreement with other studies.…”
Section: Effectiveness Of Concussion Education and Trainingcontrasting
confidence: 46%
“…Such programs may need to extend beyond a simple provision of information to the athlete and instead be directed at improving reporting intentions by addressing attitudes, beliefs, and culture. 4,[6][7][8]10,11,17,28 Additionally, it may be equally important for evidence-based education to be directed at coaches and parents, who serve as authority figures for student-athletes and whose attitudes and beliefs likely play a strong role in an athlete's decision to report or not report a concussion. 4,10,11,31 Limitations This study was a natural experiment.…”
Section: Effectiveness Of Concussion Education and Trainingmentioning
confidence: 99%
“…All studies included in this review developed a unique questionnaire based upon the literature, consensus statements, position statements, educational resources (e.g., CDC's Heads Up materials), Sport Concussion Assessment Tool (SCAT), and/or expert opinions. Five studies adopted and/or slightly modified a previously utilized survey (Anderson, Gittelman, Mann, Cyriac, & Pomerantz, 2016;Gourley, Valovich McLeod, & Bay, 2010;Kurowski, Pomerantz, Schaiper, & Gittelman, 2014;Kurowski, Pomerantz, Schaiper, Ho, & Gittelman 2015;Shroyer & Stewart, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Bloodgood et al (2013) revealed that only a quarter of both athletes and parents knew a concussion can be caused by a blow other than to the head. Similarly, other studies suggested knowledge deficits (i.e., only 58-61% of respondents answered correctly) in understanding the causes of concussions among parents (Mannings et al, 2014) and athletes (Kurowski et al, 2014;Kurowski et al, 2015).…”
Section: Youth Concussion Factsmentioning
confidence: 99%
See 1 more Smart Citation